A foldable wave absorbing material and a preparation method thereof
By using specific polyurethane resins and soft magnetic powders in the absorbing materials and rationally preparing vulcanizing agents, the problem of easy breakage after repeated bending is solved, and the excellent foldability and good flexibility of the absorbing materials are achieved, meeting the needs of flexible electronic technology.
Patent Information
- Application Number
- CN202411338613.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-09-25
AI Technical Summary
Existing absorbing materials are prone to breaking or cracking after repeated bending, and cannot meet the foldability and durability requirements of flexible electronic technology.
A repeatable bending absorbing material is prepared by introducing polyurethane resin with specific softening points, hardness and crystallization time, and combining with an appropriate amount of vulcanizing agent and soft magnetic powder. The polyurethane resin of this material includes two types: polyether type and polyester type, with a mass ratio of 6:4, polytetrahydrofuran is introduced into the soft section, soft magnetic powder includes ferrosilicon aluminum, etc., and vulcanizing agents include sulfur and di-tert-butyl peroxide, etc.
The prepared absorbent material does not delaminate or crack when repeatedly bent 0°~180°. It has excellent foldability and good flexibility, which significantly improves folding resistance and service life.
Smart Images

Figure CN118852865B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electromagnetic materials, and in particular relates to a foldable wave-absorbing material and a preparation method thereof. Background Art
[0002] Flexible electronic technology is realized through special materials and device preparation technology, which makes it uniquely flexible and ductile, allowing electronic devices to bend, fold, twist, compress or stretch within a certain range and continue to work normally. The development of flexible electronic technology not only integrates technologies in the fields of electronic circuits, electronic components, materials, flat-panel displays, nanotechnology, etc., but also spans industries such as semiconductors, packaging and testing, materials, chemicals, printed circuit boards, and display panels. It is expected to transform traditional industries, enhance industrial added value, and bring innovative changes to the fields of information, energy, medical care, and national defense.
[0003] Flexible sensors and flexible display technologies are different important branches of flexible electronic technology. For flexible sensors, they are usually able to detect a variety of environmental parameters such as pressure, force, bending, temperature, etc. They are not only suitable for medical, smart home, sports and health, but also play an important role in environmental testing, unmanned driving, smart manufacturing and other industries. As for flexible display technology, flexible electronic technology has broken through the limitations of traditional screen manufacturing and achieved the production of extremely thin, soft and transparent films. This flexible screen has almost no borders and can be bent at will. It is suitable for various portable electronic products and provides a high-definition and low-power experience.
[0004] From the above, we can see that the flexible electronics industry, as a future industry, is based on the high integration of carbon-based materials and optoelectronic processes. It not only poses new challenges and requirements for electromagnetic compatibility and electromagnetic anti-interference, but also puts forward new requirements for the flexibility and foldability of absorbing materials, which are key materials that can solve electromagnetic compatibility and electromagnetic anti-interference problems. The current absorbing materials cannot be bent (≥90°), and conventional absorbing materials will break or crack after repeated bending, which cannot meet the requirements of flexible electronics. Summary of the invention
[0005] In order to improve the foldability of an absorbing material, the present invention provides a foldable absorbing material and a preparation method thereof.
[0006] According to one aspect of the present invention, a foldable absorbing material is provided. Calculated by mass percentage, raw materials for preparing the foldable absorbing material include 15-25% polyurethane resin and 70-80% soft magnetic powder; wherein the softening point of the polyurethane resin is 60-80° C., the Shore hardness of the polyurethane resin is 65-80A, and the crystallization time of the polyurethane resin is 20-100 minutes; and the temperature for preparing the foldable absorbing material is not higher than 165° C.; the raw materials for preparing the foldable absorbing material also include a vulcanizing agent, and the mass content of the vulcanizing agent is 3-5% of the mass of the polyurethane resin.
[0007] The inventors found in actual production that when a polyurethane resin with a specific softening point (the softening point refers to the temperature at which the polymer begins to soften, and the thermal cracking temperature of the polyurethane resin is generally above 250°C), hardness and crystallization time (medium or fast crystallization rate) is introduced, and an appropriate amount of vulcanizing agent and soft magnetic powder are added, an absorbing material can be prepared that can be repeatedly bent (repeatedly folded 0°~180°) without delamination or breakage, and has excellent foldability and good flexibility.
[0008] Preferably, the polyurethane resin includes at least one of polyether polyurethane and polyester polyurethane. The oxygen atom in the ether bond is connected to the carbon chain more freely and can rotate more flexibly in the molecular chain. In addition, the molecular chain of polyether polyol is usually long and relatively regular, so the polyether polyurethane has good flexibility. As for polyester polyurethane, the large number of ester bonds contained in it will limit the movement of the molecular chain due to the polarity and a certain degree of rigidity. Although it will cause the flexibility of its polyester polyurethane to be relatively poor compared to polyether polyurethane, it can give the absorbing material good tensile properties and improve the undesirable phenomena such as breakage or cracking of the absorbing material.
[0009] Preferably, the polyurethane resin includes polyether polyurethane and polyester polyurethane; calculated by mass ratio, polyether polyurethane: polyester polyurethane = 6-7:3-4. By matching polyether polyurethane and polyester polyurethane, the absorbing material can have good flexibility and good tensile properties, so that the folding resistance and service life of the absorbing material are significantly improved.
[0010] Preferably, the soft segment in the polyether polyurethane includes polytetramethylene furan. Further, by preferably using polytetramethylene furan (PTMEG) as the soft segment in the polyether polyurethane is composed, since its molecular chain is more flexible, as the relative molecular mass increases, the segment becomes more flexible and the elasticity increases accordingly.
[0011] Preferably, the soft magnetic powder includes at least one of sendust, iron-nickel, chromium-iron, iron-silicon-chromium, carbonyl iron and ferrite.
[0012] Preferably, the D50 of the soft magnetic powder is 50-70 μm; and / or the thickness of the soft magnetic powder is 700-1300 nm; and / or the bulk density of the soft magnetic powder is 0.38-0.45 g / cm 3 .
[0013] Preferably, the raw materials for preparing the foldable absorbing material also include a vulcanizing agent, and the vulcanizing agent includes at least one of sulfur, 4,4'-methylenebis(2-chloroaniline) (MOCA), diisopropylbenzene peroxide (DCP), di-tert-butyl peroxide (DTBP), and di-tert-butyl peroxyisopropylbenzene (BIPB).
[0014] Preferably, the raw materials for preparing the foldable absorbing material further include a coupling agent, and the coupling agent includes at least one of a silane coupling agent and a titanate coupling agent.
[0015] Preferably, the silane coupling agent includes at least one of KH550, KH560 and vinyltriethoxysilane.
[0016] Preferably, the raw materials for preparing the foldable absorbing material also include a wetting and defoaming agent, and the wetting and defoaming agent includes at least one of DC65 water-based silicone varnish defoaming agent (Dow Corning), BYKETOL-OK (BYK), DISPERBYK-2013 (BYK), and TEGO (TEGO).
[0017] Preferably, the raw materials for preparing the foldable absorbing material further include an anti-settling agent, and the anti-settling agent includes at least one of non-ionic polyoxyethylene fatty amine (alcohol), polyoxyethylene fatty alcohol sulfate, polyglycol ether, white carbon black, and polyethylene wax.
[0018] According to another aspect of the present invention, a method for preparing the above-mentioned foldable absorbing material is provided, the method comprising the following steps: S1. mixing a polyurethane resin, a soft magnetic powder, a vulcanizing agent, an additive, and a solvent to obtain a slurry, and making the viscosity of the slurry 20000~40000mpa / s; S2. coating the slurry on the surface of a base film, and then performing a gradient drying treatment to form a dry film of the slurry; S3. subjecting the dry film to a high-temperature hot pressing treatment to obtain a foldable absorbing material, wherein in the high-temperature hot pressing treatment, the reaction temperature is 140~165°C, and the reaction pressure is 5~15MPa.
[0019] Preferably, the base film comprises a PET film.
[0020] Preferably, the gradient drying process includes a first drying stage, a second drying stage, a third drying stage, and a fourth drying stage; wherein the drying temperature of the first drying stage is 75-85°C; the drying temperature of the second drying stage is 95-105°C; the drying temperature of the third drying stage is 110-125°C; and the drying temperature of the fourth drying stage is 125-135°C. When the temperature of the first drying stage and the second drying stage is too high, the surface of the coated semi-finished product will be rough and in the shape of bubble rupture (the solvent boils in the temperature zone of the oven, and the bubbles on the surface boil); and when the temperature of the first drying stage and the second drying stage is too low, the residual rate of the solvent in the third drying stage and the fourth drying stage will be high, boiling will occur, and the surface of the product will be rough.
[0021] Preferably, in the first drying stage, the second drying stage, and the fourth drying stage, the drying time is 2 to 2.5 minutes respectively; in the third drying stage, the drying time is 4 to 5 minutes. When the drying time is too short, the residual solvent rate of the coated semi-finished product will be high, the humidity of the coated semi-finished product will be high, a large number of bubbles will be generated on the surface of the product during high-temperature hot pressing, and the normal winding of the absorbing material will be affected (the product layers will stick together). When the drying time is too long, the product will produce a slight burnt smell. At the same time, because a vulcanizing agent is added to the slurry, the coated semi-finished product will produce a semi-vulcanization phenomenon without the high temperature and high pressure stage, which seriously affects the performance of the later products and even makes it impossible to produce normally. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The magnetic permeability diagram of the foldable absorbing material provided by the processing group 1A of Example 1 of the present invention;
[0023] Figure 2 A comparison diagram of the foldable absorbing materials provided by the treatment group 1A and the comparison group 3A of Example 1 of the present invention;
[0024] Figure 3 The magnetic permeability diagram of the foldable absorbing material provided by the processing group 2D of Example 4 of the present invention;
[0025] Figure 4 This is a graph of the magnetic permeability of the foldable absorbing material provided by processing group 3D of Example 4 of the present invention. DETAILED DESCRIPTION
[0026] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention and the drawings in the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0027] Example 1
[0028] Treatment Group 1A
[0029] 1. Raw materials for preparing foldable absorbing materials
[0030] The raw materials for preparing the foldable absorbing material in this treatment group are shown in Table 1. Among them, according to the mass fraction, this treatment group also introduced 0.6 parts of wetting agent, 0.6 parts of defoaming agent, and 0.6 parts of anti-settling agent; the specific size of the soft magnetic powder introduced is: D 50 =60μm, AD=0.41g / cm 3 , T (thickness) = 950nm; the relevant physical properties of polyether polyurethane resin (brand name Lubrizol 5703) are: softening point = 72℃, Shore hardness = 74A, crystallization time = 55 minutes.
[0031] Table 1. Raw materials for preparing absorbing materials
[0032]
[0033] 2. Method for preparing foldable absorbing material
[0034] S1. After mixing the raw materials for preparing the absorbing material, the viscosity of the reaction mixture is controlled to be 25000~30000mpa / s by adding a solvent, and then dispersed at a stirring rate of 2000r / min at room temperature for 3 hours to obtain a slurry;
[0035] S2. The slurry is then coated on the surface of the base film (PET film), and a dry film with a thickness of 0.15 mm is obtained through gradient drying treatment; wherein, the drying temperature of the first drying stage in the gradient drying treatment is 80°C, and the drying time is 2.5 minutes; the drying temperature of the second drying stage is 100°C, and the drying time is 2.5 minutes; the drying temperature of the third drying stage is 120°C, and the drying time is 5 minutes; the drying temperature of the fourth drying stage is 130°C, and the drying time is 2.5 minutes.
[0036] S3. Take two of the above dry films and subject them to high-temperature hot pressing treatment to obtain a foldable absorbing material with a thickness of 0.1 mm, wherein in the high-temperature hot pressing treatment, the reaction temperature is 150° C., the reaction pressure is 8 MPa, and the reaction time is 5 minutes.
[0037] Treatment Group 2A
[0038] This treatment group prepared the foldable absorbing material with reference to the formula and method provided by treatment group 1A of Example 1. The difference from treatment group 1A of Example 1 is that when preparing the foldable absorbing material, this treatment group uses polyester polyurethane resin (brand name, manufacturer Felter 2170, softening point = 80°C, Shore hardness = 72A, crystallization time = 40 minutes) instead of polyether polyurethane resin. In addition to the above differences, the operating steps for preparing the foldable absorbing material in this treatment group are strictly consistent with those of treatment group 1A of Example 1.
[0039] Treatment Group 3A
[0040] This treatment group prepares the foldable absorbing material with reference to the formula and method provided by treatment group 1A of Example 1. The difference from treatment group 1A of Example 1 is that the polyurethane resin used in this treatment group also includes polyester polyurethane resin (brand name Huafeng 330, softening point = 65°C, Shore hardness = 79A, crystallization time = 70 minutes) when preparing the foldable absorbing material; and according to the mass ratio, the polyether polyurethane resin: polyester polyurethane resin = 5:5 (the total mass fraction of the polyurethane resin remains unchanged). In addition to the above differences, the operating steps for preparing the foldable absorbing material in this treatment group are strictly consistent with those of treatment group 1A of Example 1.
[0041] Treatment Group 4A
[0042] This treatment group prepared the foldable absorbing material with reference to the formula and method provided by treatment group 3A of Example 1. The difference from treatment group 3A of Example 1 is that when preparing the foldable absorbing material, this treatment group used a mass ratio of polyether polyurethane resin: polyester polyurethane resin = 6:4 (the total mass fraction of polyurethane resin remained unchanged). Except for the above differences, the operation steps for preparing the foldable absorbing material in this treatment group were strictly consistent with those of treatment group 3A of Example 1.
[0043] Treatment Group 5A
[0044] This treatment group prepared the foldable absorbing material with reference to the formula and method provided by treatment group 3A of Example 1. The difference from treatment group 3A of Example 1 is that when preparing the foldable absorbing material, this treatment group used a mass ratio of polyether polyurethane resin: polyester polyurethane resin = 7:3 (the total mass fraction of polyurethane resin remains unchanged). Except for the above differences, the operation steps for preparing the foldable absorbing material in this treatment group are strictly consistent with those of treatment group 3A of Example 1.
[0045] Treatment Group 6A
[0046] This treatment group prepared the foldable absorbing material with reference to the formula and method provided by treatment group 3A of Example 1. The difference from treatment group 3A of Example 1 is that when preparing the foldable absorbing material, this treatment group used a mass ratio of polyether polyurethane resin: polyester polyurethane resin = 8:2 (the total mass fraction of polyurethane resin remained unchanged). Except for the above differences, the operation steps for preparing the foldable absorbing material in this treatment group were strictly consistent with those of treatment group 3A of Example 1.
[0047] Treatment Group 7A
[0048] This treatment group prepared the foldable absorbing material with reference to the formula and method provided by treatment group 1A of Example 1. The difference from treatment group 1A of Example 1 is that the polyether polyurethane resin used in the preparation of the foldable absorbing material by this treatment group is (its soft segment does not include PTMEG, softening point = 70°C, Shore hardness = 75A, crystallization time = 100 minutes). Except for the above differences, the operation steps of preparing the foldable absorbing material by this treatment group are strictly consistent with those of treatment group 1A of Example 1.
[0049] Comparative Group 1A
[0050] This comparative group prepared the foldable absorbing material by referring to the formula and method provided by the treatment group 1A of Example 1. The difference from the treatment group 1A of Example 1 is that the polyether polyurethane resin used in the preparation of the foldable absorbing material in this comparative group is (brand name, manufacturer BASF 1160A, softening point = 80°C, Shore hardness = 82A, crystallization time = 120 minutes). Except for the above differences, the operation steps for preparing the foldable absorbing material in this comparative group are strictly consistent with those of the treatment group 1A of Example 1.
[0051] Comparative Group 2A
[0052] This comparative group prepared the foldable absorbing material by referring to the formula and method provided by the treatment group 1A of Example 1. The difference from the treatment group 1A of Example 1 is that when preparing the foldable absorbing material, the mass content of the polyether polyurethane resin in this comparative group is 30% (at the same time, the mass content of the soft magnetic powder in the formula is 70-80%). Except for the above differences, the operation steps for preparing the foldable absorbing material in this comparative group are strictly consistent with those of the treatment group 1A of Example 1.
[0053] Comparative group 3A
[0054] This comparative group prepared the foldable absorbing material by referring to the formula and method provided by the treatment group 1A of Example 1. The difference from the treatment group 1A of Example 1 is that when preparing the foldable absorbing material, the mass content of the polyether polyurethane resin in this comparative group is 10% (at the same time, the mass content of the soft magnetic powder in the formula is 70-80%). Except for the above differences, the operation steps for preparing the foldable absorbing material in this comparative group are strictly consistent with those of the treatment group 1A of Example 1.
[0055] Test Example 1
[0056] 1. Test subjects
[0057] The absorbing materials prepared in each treatment group and comparison group provided in Example 1.
[0058] 2. Test Method
[0059] This test example was carried out according to the following method, wherein the temperature and humidity of the test room were controlled as follows: temperature 23°C ± 3°C; humidity: 50RH ± 10%.
[0060] (1) Magnetic permeability: The test object was cut into a ring with an inner diameter of 9 mm and an outer diameter of 16 mm on a mold and tested on an E4991B precision impedance analyzer.
[0061] (2) Stiffness: Cut the test object into samples of 7 cm*3.8 cm and test it on a bending stiffness tester.
[0062] (3) Density: The density of the test object is tested using the Archimedes drainage method.
[0063] (4) Bending performance: Cut the test object into A4 size, and then fold it in half 50 times to observe whether it breaks when folded and whether the broken part of the product is delaminated. "O" indicates that the test result of the test object is no cracking and no delamination; "X" indicates that the test result of the test object is cracking and no delamination, no cracking and delamination, or cracking and delamination.
[0064] (5) Appearance: Observe the surface condition of the test object visually, with the naked eye within a distance of 30 cm to 45 cm from the object. "O" indicates that the test object is smooth, free of particles and free of bubbles; "X" indicates that the test object is not smooth, has particles or has bubbles.
[0065] 3. Test results and analysis
[0066] The test results of this test example are shown in Table 2. In this test example, the influence of polyurethane resin on the absorbing material is mainly explored. Among them, in the test results of treatment groups 1A~7A and comparison group 1A, it can be found that the introduction of different polyurethane resins will affect the foldability of the absorbing material, and the physical and chemical properties of polyurethane such as softening point, hardness, and crystallization time will also affect the foldability of the absorbing material. Among them, the magnetic permeability test graph of treatment group 1A is shown in Figure 1 As shown (μ' represents magnetic permeability, μ' represents the real part of relative magnetic permeability; μ" represents the imaginary part of relative magnetic permeability; μ' characterizes the degree of response of the material to the magnetic flux under the action of the magnetic field, and represents the magnetization intensity of the material in the magnetic field; μ" characterizes the material's ability to absorb or radiate the magnetic field, and represents the loss characteristics of the material).
[0067] Moreover, the experimental data shown in Table 2 confirm that the absorbing materials prepared in treatment groups 1A~7A will not break or delaminate when folded 50 times. Furthermore, when the number of foldings reaches 60 times, treatment groups 2A~3A and treatment groups 6A~7A will break or delaminate. This may be because when polyether polyurethane resin and polyester polyurethane resin are introduced at the same time and the mass ratio of the two is controlled to be 6~7:3~4, the foldability and tensile properties of the absorbing material can be further improved. By reasonably regulating the mass ratio of the two, the absorbing material can have good flexibility and good tensile properties, which significantly improves the folding resistance and service life of the absorbing material. In addition, when the soft segment in the polyether polyurethane is introduced into PTMEG, the flexibility of the absorbing material can be further enhanced.
[0068] It can be seen from the treatment group 1A and the comparison groups 2A~3A that when the resin content is too high or too low, it will affect the foldability of the absorbing material, causing it to crack or delaminate. The delamination phenomenon is similar to the non-delamination phenomenon. Figure 2 shown.
[0069] Table 2. Test data for this test case
[0070]
[0071] Example 2
[0072] Treatment Group 1B
[0073] This treatment group prepared the foldable absorbing material according to the formula and method provided by treatment group 1A in Example 1.
[0074] Treatment Group 2B
[0075] This treatment group prepared the foldable absorbing material with reference to the formula and method provided by treatment group 1B of Example 2. The difference from treatment group 1B of Example 2 is that when preparing the foldable absorbing material, the amount of vulcanizing agent used in this treatment group is 3% of the polyurethane resin (the mass ratio of sulfur to DTBP is 1:1, and at the same time, the formula is made to meet the requirements of 15-25% mass content of polyurethane resin and 70-80% mass content of soft magnetic powder). Except for the above differences, the operation steps of preparing the foldable absorbing material in this treatment group are strictly consistent with those of treatment group 1B of Example 2.
[0076] Treatment Group 3B
[0077] This treatment group prepared the foldable absorbing material with reference to the formula and method provided by treatment group 1B of Example 2. The difference from treatment group 1B of Example 2 is that when preparing the foldable absorbing material, the total amount of vulcanizing agent used in this treatment group is 5% of the polyurethane resin (the mass ratio of sulfur to DTBP is 1:1, and at the same time, the formula is made to meet the requirements of 15-25% mass content of polyurethane resin and 70-80% mass content of soft magnetic powder). Except for the above differences, the operation steps of preparing the foldable absorbing material in this treatment group are strictly consistent with those of treatment group 1B of Example 2.
[0078] Treatment Group 4B
[0079] This treatment group prepared the foldable absorbing material with reference to the formula and method provided by treatment group 1B of Example 2. The difference from treatment group 1B of Example 2 is that when preparing the foldable absorbing material, this treatment group replaced DTBP with sulfur in equal parts by mass (sulfur was used only as a vulcanizing agent). Except for the above differences, the operation steps for preparing the foldable absorbing material by this treatment group were strictly consistent with those of treatment group 1B of Example 2.
[0080] Treatment Group 5B
[0081] This treatment group prepared the foldable absorbing material with reference to the formula and method provided by treatment group 1B of Example 2. The difference from treatment group 1B of Example 2 is that when preparing the foldable absorbing material, this treatment group replaced sulfur with an equal mass fraction of DTBP (only DTBP was used as a vulcanizing agent). Except for the above differences, the operation steps for preparing the foldable absorbing material by this treatment group were strictly consistent with those of treatment group 1B of Example 2.
[0082] Treatment Group 6B
[0083] This treatment group prepared the foldable absorbing material with reference to the formula and method provided by treatment group 1B of Example 2. The difference from treatment group 1B of Example 2 is that when preparing the foldable absorbing material, this treatment group replaced DTBP and sulfur with equal mass fractions of MOCA (only MOCA was used as a vulcanizing agent). Except for the above differences, the operation steps for preparing the foldable absorbing material by this treatment group were strictly consistent with those of treatment group 1B of Example 2.
[0084] Comparative group 1B
[0085] This comparative group prepares the foldable absorbing material with reference to the formula and method provided by the treatment group 1B of Example 2. The difference from the treatment group 1B of Example 2 is that when preparing the foldable absorbing material, the mass fraction of the vulcanizing agent in this comparative group is reduced, so that the vulcanizing agent is 2% of the mass of the polyurethane resin (the mass ratio of sulfur to DTBP is 1:1, and at the same time, the formula is made to meet the requirements that the mass content of the polyurethane resin is 15-25%, and the mass content of the soft magnetic powder is 70-80%). In addition to the above differences, the operating steps for preparing the foldable absorbing material in this comparative group are strictly consistent with those of the treatment group 1B of Example 2.
[0086] Comparative group 2B
[0087] This comparative group prepares the foldable absorbing material with reference to the formula and method provided by the treatment group 1B of Example 2. The difference from the treatment group 1B of Example 2 is that when preparing the foldable absorbing material, the mass fraction of the vulcanizing agent in this comparative group is reduced, so that the vulcanizing agent is 6% of the mass of the polyurethane resin (the mass ratio of sulfur to DTBP is 1:1, and at the same time, the formula is made to meet the requirements that the mass content of the polyurethane resin is 15-25% and the mass content of the soft magnetic powder is 70-80%). In addition to the above differences, the operating steps for preparing the foldable absorbing material in this comparative group are strictly consistent with those of the treatment group 1B of Example 2.
[0088] Test Example 2
[0089] 1. Test subjects
[0090] The absorbing materials prepared in each treatment group and the comparison group of Example 2.
[0091] 2. Test Method
[0092] This test example was performed with reference to the method provided in Test Example 1.
[0093] 3. Test results and analysis
[0094] The results of this test example are shown in Table 3. In this test example, the effect of the vulcanizing agent on the foldable performance of the absorbing material is mainly explored. Among them, it can be seen from the treatment groups 1B~3B and the comparison groups 1B~2B that the amount of the vulcanizing agent will significantly affect the foldable performance of the absorbing material. Through experiments, it was found that when the amount of the vulcanizing agent is too high, the hardness of the absorbing material obtained will increase, resulting in the problem of breaking immediately after bending; and when the amount of the vulcanizing agent is too low, the mechanical properties of the absorbing material obtained will be reduced, resulting in the problem of delamination and making the surface of the absorbing material very rough.
[0095] By comparing treatment group 1B and treatment groups 4B~6B, it can be seen that different vulcanizers will also affect the stiffness of the absorbing material. Through experiments, it is found that the combination of multiple vulcanizers helps to improve the stiffness of the foldable absorbing material, so that it can maintain the effect of being able to achieve repeated bending.
[0096] Table 3. Test data for this test case
[0097]
[0098] Example 3
[0099] Treatment Group 1C
[0100] This treatment group prepared the foldable absorbing material according to the formula and method provided by treatment group 1A in Example 1.
[0101] Treatment Group 2C
[0102] This treatment group prepared the foldable absorbing material with reference to the formula and method provided by treatment group 1C of Example 3. The difference from treatment group 1C of Example 3 is that when preparing the foldable absorbing material, the reaction temperature of this treatment group during the high-temperature hot pressing process is 165° C. In addition to the above differences, the operation steps of preparing the foldable absorbing material by this treatment group are strictly consistent with those of treatment group 1C of Example 3.
[0103] Treatment Group 3C
[0104] This treatment group prepared the foldable absorbing material with reference to the formula and method provided by treatment group 1C of Example 3. The difference from treatment group 1C of Example 3 is that when preparing the foldable absorbing material, the reaction temperature of this treatment group during the high-temperature hot pressing process is 135° C. In addition to the above differences, the operation steps of preparing the foldable absorbing material by this treatment group are strictly consistent with those of treatment group 1C of Example 3.
[0105] Treatment Group 4C
[0106] This treatment group prepared the foldable absorbing material with reference to the formula and method provided by treatment group 1C of Example 3. The difference from treatment group 1C of Example 3 is that when preparing the foldable absorbing material, the reaction temperature of this treatment group during the high-temperature hot pressing process is 120° C. In addition to the above differences, the operation steps of preparing the foldable absorbing material by this treatment group are strictly consistent with those of treatment group 1C of Example 3.
[0107] Comparative group 1C
[0108] This comparative group prepared the foldable absorbing material by referring to the formula and method provided by treatment group 1C of Example 3. The difference from treatment group 1C of Example 3 is that when preparing the foldable absorbing material, the reaction temperature of this comparative group in the high-temperature hot pressing process is 175° C. In addition to the above differences, the operation steps for preparing the foldable absorbing material of this comparative group are strictly consistent with those of treatment group 1C of Example 3.
[0109] Comparative group 2C
[0110] This treatment group prepares the foldable absorbing material with reference to the formula and method provided by treatment group 1C of Example 3. The difference from treatment group 1C of Example 3 is that the gradient drying treatment of this treatment group is three-stage drying when preparing the foldable absorbing material. In addition to the above differences, the operation steps of preparing the foldable absorbing material by this treatment group are strictly consistent with those of treatment group 1C of Example 3. Specifically, the gradient drying treatment of this treatment group is: the drying temperature of the first drying stage is 90°C and the drying time is 2.5 minutes; the drying temperature of the second drying stage is 110°C and the drying time is 7.5 minutes; the drying temperature of the third drying stage is 130°C and the drying time is 2.5 minutes.
[0111] Test Example 3
[0112] 1. Test subjects
[0113] The absorbing materials prepared in each treatment group and the comparison group of Example 3.
[0114] 2. Test Method
[0115] This test example was performed with reference to the method provided in Test Example 1.
[0116] 3. Test results and analysis
[0117] The results of this test example are shown in Table 4. In this test example, the effect of the preparation method on the foldable performance of the absorbing material is mainly explored. Among them, it can be found in treatment group 1C to treatment group 4C and comparison group 1C that the reaction temperature in the high-temperature hot pressing treatment will also affect the bending performance of the absorbing material. This is because the reaction temperature will affect the crosslinking degree of the polyurethane resin and the vulcanizing agent in the product. Generally speaking, the lower the crosslinking degree, the lower the stiffness of the product. By comparing treatment group 1C with treatment group 2C, it can be found that the gradient drying treatment will also affect the appearance of the prepared absorbing material, resulting in a rough surface of the prepared absorbing material.
[0118] Table 4. Test data for this test case
[0119]
[0120] Example 4
[0121] Treatment Group 1D
[0122] This treatment group prepared the foldable absorbing material according to the formula and method provided by treatment group 1A in Example 1.
[0123] Treatment Group 2D
[0124] This treatment group prepared the foldable absorbing material with reference to the formula and method provided by treatment group 1D of Example 4. The difference from treatment group 1D of Example 4 is that when preparing the foldable absorbing material, the mass content of the soft magnetic powder in the raw material is 70% (at the same time, the formula is made to meet the requirements that the mass content of the polyurethane resin is 15-25%, and the mass content of the vulcanizing agent is 3-5% of the mass of the polyurethane resin). Except for the above differences, the operation steps of preparing the foldable absorbing material by this treatment group are strictly consistent with those of treatment group 1D of Example 4.
[0125] Treatment Group 3D
[0126] This treatment group prepared the foldable absorbing material with reference to the formula and method provided by treatment group 1D of Example 4. The difference from treatment group 1D of Example 4 is that when preparing the foldable absorbing material, the mass content of the soft magnetic powder in the raw material is 80% (at the same time, the formula is made to meet the requirements that the mass content of the polyurethane resin is 15-25%, and the mass content of the vulcanizing agent is 3-5% of the mass of the polyurethane resin). Except for the above differences, the operation steps of preparing the foldable absorbing material by this treatment group are strictly consistent with those of treatment group 1D of Example 4.
[0127] Treatment Group 4D
[0128] This treatment group prepared the foldable absorbing material by the formula and method provided by the treatment group 1D of Example 4. The difference from the treatment group 1D of Example 4 is that the AD of the soft magnetic powder used in the preparation of the foldable absorbing material in this treatment group is 0.38 g / cm 3 , D 50 The thickness is 70 μm and 1000 nm. Except for the above differences, the operation steps of preparing the foldable absorbing material in this treatment group are strictly consistent with those of treatment group 1D in Example 4.
[0129] Treatment Group 5D
[0130] This treatment group prepared the foldable absorbing material by referring to the formula and method provided by treatment group 1D of Example 4. The difference from treatment group 1D of Example 4 is that the AD of the soft magnetic powder used in this treatment group when preparing the foldable absorbing material is 0.43 g / cm 3 , D 50 The thickness is 50 μm and 800 nm. Except for the above differences, the operation steps of preparing the foldable absorbing material in this treatment group are strictly consistent with those of treatment group 1D in Example 4.
[0131] Treatment Group 6D
[0132] This treatment group prepared the foldable absorbing material by the formula and method provided by the treatment group 1D of Example 4. The difference from the treatment group 1D of Example 4 is that the AD of the soft magnetic powder used in the preparation of the foldable absorbing material in this treatment group is 0.49 g / cm 3 , D 50 The thickness is 45 μm and 700 nm. Except for the above differences, the operation steps of preparing the foldable absorbing material in this treatment group are strictly consistent with those of treatment group 1D in Example 4.
[0133] Treatment Group 7D
[0134] This treatment group prepared the foldable absorbing material by the formula and method provided by the treatment group 1D of Example 4. The difference from the treatment group 1D of Example 4 is that the AD of the soft magnetic powder used in the preparation of the foldable absorbing material in this treatment group is 0.36 g / cm 3 , D 50 The thickness is 77 μm and 900 nm. Except for the above differences, the operation steps of preparing the foldable absorbing material in this treatment group are strictly consistent with those of treatment group 1D in Example 4.
[0135] Comparative group 1D
[0136] This comparative group prepared the foldable absorbing material by referring to the formula and method provided by the treatment group 1D of Example 4. The difference from the treatment group 1D of Example 4 is that when preparing the foldable absorbing material, the mass content of the soft magnetic powder in the raw material is 81% (at the same time, the formula is made to meet the requirements of the mass content of the polyurethane resin being 15-25% and the mass content of the vulcanizing agent being 3-5% of the mass of the polyurethane resin). Except for the above differences, the operation steps for preparing the foldable absorbing material in this comparative group are strictly consistent with those of the treatment group 1D of Example 4.
[0137] Comparison group 2D
[0138] This comparative group prepared the foldable absorbing material by referring to the formula and method provided by the treatment group 1D of Example 4. The difference from the treatment group 1D of Example 4 is that when preparing the foldable absorbing material, the mass content of the soft magnetic powder in the raw material is 63% (at the same time, the formula is made to meet the mass content of the polyurethane resin of 15-25% and the mass content of the vulcanizing agent of 3-5% of the mass of the polyurethane resin). Except for the above differences, the operation steps of preparing the foldable absorbing material in this comparative group are strictly consistent with those of the treatment group 1D of Example 4.
[0139] Test Example 4
[0140] 1. Test subjects
[0141] The absorbing materials prepared in each treatment group and the comparison group of Example 4.
[0142] 2. Test Method
[0143] This test example was performed with reference to the method provided in Test Example 1.
[0144] 3. Test results and analysis
[0145] The results of this test example are shown in Table 5. In this test example, the main purpose is to explore the effect of soft magnetic powder on the foldability and magnetic permeability of the absorbing material. Among them, it can be found in the treatment groups 1D~2D and the comparison groups 1D~2D that the content of soft magnetic powder not only affects the magnetic permeability, but also affects the foldability of the absorbing material. Therefore, in order to make the absorbing material have good bending properties, the mass content of soft magnetic powder needs to be adjusted to 70~80%. The magnetic permeability test chart of treatment group 2D is as follows Figure 3 shown.
[0146] In addition, the test data of treatment group 1D and treatment groups 4D~7D show that the particle size of soft magnetic powder will also affect the magnetic permeability performance of the absorbing material. Therefore, by adjusting the particle size of soft magnetic powder, the absorbing material can maintain good bending performance while also having good magnetic permeability. The magnetic permeability test graph of treatment group 3D is shown in Figure 2. Figure 4 shown.
[0147] Table 5. Test data for this test case
[0148]
[0149] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A foldable absorbing material, characterized in that: Calculated by mass percentage, the raw materials for preparing the foldable absorbing material include 15-25% polyurethane resin and 70-80% soft magnetic powder; The softening point of the polyurethane resin is 60-80° C., the Shore hardness of the polyurethane resin is 65-80A, and the crystallization time of the polyurethane resin is 20-100 minutes. The D50 of the soft magnetic powder is 50-70 μm, the thickness of the soft magnetic powder is 700-1300 nm, and the bulk density of the soft magnetic powder is 0.38-0.45 g / cm3; The raw materials for preparing the foldable absorbing material also include a vulcanizing agent, and the mass content of the vulcanizing agent is 3-5% of the mass of the polyurethane resin; The method for preparing the foldable absorbing material comprises the following steps: S1. The polyurethane resin, the soft magnetic powder, the vulcanizing agent, the additive, and the solvent are mixed to obtain a slurry, and the viscosity of the slurry is 20000~40000mpa / s; S2. After the slurry is coated on the surface of the base film, the slurry is formed into a dry film by gradient drying; wherein the gradient drying process includes a first drying stage, a second drying stage, a third drying stage, and a fourth drying stage; the drying temperature of the first drying stage is 75-85°C; the drying temperature of the second drying stage is 95-105°C; the drying temperature of the third drying stage is 110-125°C; the drying temperature of the fourth drying stage is 125-135°C; S3. The dry film is subjected to high-temperature hot pressing treatment to obtain the foldable absorbing material, wherein, in the high-temperature hot pressing treatment, the reaction temperature is 140~165℃, and the reaction pressure is 5~15MPa.
2. The foldable absorbing material according to claim 1, characterized in that: The polyurethane resin includes at least one of polyether polyurethane and polyester polyurethane.
3. The foldable absorbing material according to claim 2, characterized in that: The polyurethane resin includes the polyether polyurethane and the polyester polyurethane; calculated by mass ratio, the polyether polyurethane: the polyester polyurethane = 6~7:3~4.
4. The foldable absorbing material according to claim 2 or 3, characterized in that: The soft segment in the polyether polyurethane includes polytetrahydrofuran.
5. The foldable absorbing material according to claim 1, characterized in that: The soft magnetic powder includes at least one of sendust, iron-nickel, chromium-iron, iron-silicon-chromium, carbonyl iron and ferrite.
6. The foldable absorbing material according to claim 1, characterized in that: The raw materials for preparing the foldable absorbing material also include a vulcanizing agent, and the vulcanizing agent includes at least one of sulfur, 4,4'-methylenebis(2-chloroaniline), diisopropylbenzene peroxide, di-tert-butyl peroxide, and di-tert-butyl peroxyisopropylbenzene.
7. The foldable absorbing material according to claim 1, characterized in that: In the first drying stage, the second drying stage and the fourth drying stage, the drying time is 2 to 2.5 minutes respectively; in the third drying stage, the drying time is 4 to 5 minutes.
Citation Information
Patent Citations
Rubber film, preparation method of rubber film, electromagnetic-wave absorbing prepreg material, and preparation method and applications of electromagnetic-wave absorbing prepreg material
CN106336613A
Wave-absorbing heat-conducting flexible composite material and preparation method thereof
CN111621139A